Analysis of Public Transportation User Dynamics Regarding Balikpapan City Trans (BaCitra) Policy - Tjang Meike Theresia Chen; Christopher Davito Prabandewa Hertadi; Alvin Muhammad ‘ Ainul Yaqin (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
The emergence of Balikpapan City Trans (BaCitra) as a new mode of transportation has caused concern among public transportation (Public Transportation) drivers due to a decline in passenger numbers. This study aims to analyze the impact of BaCitra's presence on public transportation usage using a Dynamic System approach. The analysis was conducted to identify factors influencing mode choice, develop a Causal Loop Diagram (CLD) and Stock and Flow Diagram (SFD), and formulate improvement strategies that could create intermodal balance. Based on existing modeling results, within five years the number of Public Transportation passengers decreased from 9,516 to 4,228 passengers, while the number of BaCitra users increased from 8,125 to 21,447 passengers. This imbalance led to the formulation of seven improvement scenarios. Scenario 7, which is a combination of increasing BaCitra fares and maximizing Public Transportation safety and comfort (value 1), is considered the most effective scenario. The implementation of this scenario resulted in 15,523 Public Transportation passengers and 14,112 BaCitra passengers. The results of the study show that this combined strategy is able to create a balance in the choice of transportation modes by the community, so that Public Transportation can continue to operate without sacrificing the quality of BaCitra services.